Merging of ERS-1, ERS-2 and Envisat altimeter data over the Greenland ice sheet - Khvorostovsky, Kirill; Johannessen Ola M. (Zenodo, 2009)
Greenland ice sheet elevation changes for 16.5-year time period from 1992 to 2008 were analyzed from ERS-1, ERS-2 and Envisat satellite radar altimeter data. Development of the method for determination inter-satellite biases was performed for merging radar altimeter measurements from different satellites and creating continuous time series. Inter-satellite biases for elevation and backscattered coefficient have shown to be significantly effected by the bias between measurements in ascending and descending orbits. Adjusting elevation time series for correlation between elevation and backscattered power changes over Greenland ice sheet significantly lowered elevation change rate estimates and resulted in consistency between radar and laser altimeter results. Detailed analysis of this correction revealed its essential dependence on temporal variations of the correlation gradient between elevation and backscattered power in addition to variations of backscattered power. As the correction represents changes in scattering characteristics of the ice sheet, its applying is likely able to correct elevation change estimates for penetration of part of the radar altimeter signal through the surface. Over 76% of Greenland ice sheet area elevation change rate of 0.8±0.3 cm/year from 1992 to 2008 was found. Increases in surface elevation, which were observed over the high-elevation regions of Greenland from 1995 have decelerated over the period from 2003 to 2005 and changed to elevation decrease during 2006-2008. For the whole period 1992-2008 elevation increase is 1.8±0.2 cm/year over 87% of the areas above 1500 m. In contrast, over 38% of the low-elevation areas below 1500 m rate of elevation change is -7.1±1.1 cm/year and surface-elevation decreases that started from 2000 have continued NERSC Technical Report no. 307